2018
DOI: 10.2471/blt.17.206227
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of diabetes screening methods used for people with tuberculosis, Indonesia, Peru, Romania, South Africa

Abstract: ObjectiveTo evaluate the performance of diagnostic tools for diabetes mellitus, including laboratory methods and clinical risk scores, in newly-diagnosed pulmonary tuberculosis patients from four middle-income countries.MethodsIn a multicentre, prospective study, we recruited 2185 patients with pulmonary tuberculosis from sites in Indonesia, Peru, Romania and South Africa from January 2014 to September 2016. Using laboratory-measured glycated haemoglobin (HbA1c) as the gold standard, we measured the diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
(42 reference statements)
1
27
0
Order By: Relevance
“…However, unlike recent data from a multi-country study investigating diabetes in TB (the TANDEM study), we did not observe an association between diabetes and previous TB or with smear positive cases 31 . The distribution of HbA1c values for our diabetic population (new and previously diagnosed cases) was also similar to that from the Indonesian TANDEM study population, in whom a single point of care (POC) HbA1c test was shown to have high sensitivity and specificity to detect new diabetes cases, adding confidence to our diagnoses of diabetes using this single POC measurement 41 .…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, unlike recent data from a multi-country study investigating diabetes in TB (the TANDEM study), we did not observe an association between diabetes and previous TB or with smear positive cases 31 . The distribution of HbA1c values for our diabetic population (new and previously diagnosed cases) was also similar to that from the Indonesian TANDEM study population, in whom a single point of care (POC) HbA1c test was shown to have high sensitivity and specificity to detect new diabetes cases, adding confidence to our diagnoses of diabetes using this single POC measurement 41 .…”
Section: Discussionsupporting
confidence: 60%
“…We thus investigated how, in resource-limited settings, waist-to-hip ratio might be useful as a screening tool for prioritising individuals for diabetes testing and observed a high sensitivity of 87% for a single cut-off for both sexes, supporting its potential use, at least in the Filipino context. Mean waist to hip ratio was also significantly increased in the TANDEM study, and most significantly in Indonesia 31 , although neither waist to hip ratio or waist circumference were included in the final multicountry predictive risk score for diabetes in persons with TB 41 .…”
Section: Discussionmentioning
confidence: 90%
“…At 21%, the prevalence of intermediate hyperglycaemia ("pre-diabetes") identified in TB patients was higher than expected, although a rising prevalence of intermediate hyperglycaemia has been reported in LMICs [31]. This figure would have even been higher based on point-of-care HbA1c results [10], or use of the lower American Diabetes Supplementary Figure 1) [9]. The definition of intermediate hyperglycaemia itself is under scrutiny as DM only develops within 10 years in <50% of those identified with pre-DM based on a single FBG or HbA1c test [33], and uncertainty about the cut-point when using HbA1c.…”
Section: Discussionmentioning
confidence: 89%
“…We defined individuals with pulmonary TB if they initiated treatment at a local TB program, based on bacteriological (sputum smear, sputum culture or Xpert test), radiological and/or clinical evidence. Further details are published elsewhere [9,10] and are freely available in online appendices [8].…”
Section: Study Measurements and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation